The Source Value of Tafsir al-Jalaleyn in the interpretive translation attributed to Akif (in the Example of Surah al-Fatiha and al-Baqarah) - Seferoglu, Murad (Scholarya Demo Journal of Ruby, 2023)
The subject of our article is to explore the similarities between the Tafsir al-Jalaleyn and the interpretive translation attributed to Mehmet Akif Ersoy, as well as the extent of his utilization of the Tafsir al-Jalaleyn, specifically focusing on Surahs al-Fatiha and al-Baqarah. Mehmet Akif’s interpretive translation spans from Surah al-Fatiha to the end of Sura al-Tawba. Unlike translations written during that period, Mehmet Akif's translation prominently features a literary style. Despite facing numerous challenges, including living abroad in Egypt for many years, Mehmet Akif composed his translation, which remained undisclosed for almost a quarter of a century. After concerns were alleviated, the translation was published and gained recognition in journals, theses, articles, and encyclopedias, piquing the curiosity of researchers.             It is reported that Mehmet Akif read the Tafsir al-Jalaleyn nineteen times. Consequently, it is necessary for our article also to include information about Mahalli and Suyuti, the authors of Tafsir al-Jalaleyn. The research begins with brief information regarding both authors of Tafsir al-Jalaleyn, their academic backgrounds, and Mehmet Akif's interpretive translation. Subsequently, Mehmet Akif's translation of the Quran and the methodology he followed in this translation are examined. Following these introductory reminders, Mehmet Akif's interpretive translation of the Quran is compared to Tafsir al-Jalaleyn within the context of Surah Al-Fatiha and Surah Al-Baqarah. In this comparison, findings have been obtained regarding the extent to which Mehmet Akif utilized Tafsir al-Jalaleyn and the degree of similarities observed.                Findings regarding the extent to which Mehmet Akif utilized Tafsir al-Jalaleyn, and identification of similarities between the two have been obtained in this comparative analysis. Based on these findings, a special interest, similarity, preference, reference, or parallelism to Tafsir al-Jalaleyn have been observed in interpretive translation attributed to Mehmet Akif. However, it should also be noted that Mehmet Akif's interest in or allegiance to Tafsir al- Jalaleyn in his interpretive translation was not blind. He blended the method of Tafsir al-Jalaleyn with his own unique method and style in his translation.